Narrativas Sobre Las Relaciones Parentales, La Dinámica con Pares Y Proyecto De Vida En Adolescentes De La Comunidad Nasa Que Consumen Sustancias Psicoactivas - Galeano González, Jeimmy Sthephanya; Cuchillo Chilo, Karen Viviana (Universidad Antonio Nariño, 2024)
The purpose of this research is to analyze the different narratives of two adolescent users of psychoactive substances belonging to the Nasa indigenous community in the department of Cauca, specifically in the municipality of Caldono. In order to carry out this project, a qualitative methodology was used together with a data collection technique called free interview, which aims to hold open conversations with the interviewees on various topics. This allowed us to obtain information on the perspectives of these adolescents in relation to PAS use and its impact on parental relationships, peer dynamics and their life project.